Comment on “Organelles Ca²⁺ redistribution contributes to cadmium-induced EMT of renal cancer cells through p-cPLA2-mediated arachidonic acid release” - Jiaqi Liang; Guangzhen Wu (Ecotoxicology and Environmental Safety, 2025)
This commentary proposes enhancements to improve a study on cadmium-induced EMT in renal cancer cells. Key recommendations encompass the following aspects: Supplementing statistical power justification through explicit definition of parameters including ≥80% desired power, minimal effect size, and intra-group variability; Report exact P values with confidence intervals to improve statistical transparency; Clarification of p38 MAPK versus cPLA2 pathway contributions via co-inhibition experiments; Exclusion of TRP channel confounding effects when using 2-APB through targeted TRPV6 inhibition; Distinction between direct Cd²⁺ effects and toxicity-induced compensatory responses; Provision of explicit rationale for selecting Mag-Fluo-4/AM and Rhod-2/AM fluorescent probes; Experimental verification of PMCA inhibition synergism with cadmium-induced cytosolic Ca²⁺ overload. These recommendations would enhance the robustness of the original study's conclusions.